MicroRNA160 Modulates Plant Development and Heat Shock Protein Gene Expression to Mediate Heat Tolerance in Arabidopsis - Lin, Jeng-Shane; Kuo, Chia-Chia; Yang, I-Chu; Tsai, Wei-An; Shen, Yu-Hsing; Lin, Chih-Ching; Liang, Yi-Chen; Li, Yu-Chi; Kuo, Yun-Wei; King, Yu-Chi; Lai, Hsi-Mei; Jeng, Shih-Tong (Frontiers in Plant Science, 2018)
Global warming is causing a negative impact on plant growth and adversely impacts on crop yield. MicroRNAs (miRNAs) are critical in regulating the expression of genes involved in plant development as well as defense responses. The effects of miRNAs on heat-stressed Arabidopsis warrants further investigation. Heat stress increased the expression of miR160 and its precursors but considerably reduced that of its targets, ARF10, ARF16, and ARF17. To study the roles of miR160 during heat stress, transgenic Arabidopsis plants overexpressing miR160 precursor a (160OE) and artificial miR160 (MIM160), which mimics an inhibitor of miR160, were created. T-DNA insertion mutants of miR160 targets were also used to examine their tolerances to heat stress. Results presented that overexpressing miR160 improved seed germination and seedling survival under heat stress. The lengths of hypocotyl elongation and rachis were also longer in 160OE than the wild-type (WT) plants under heat stress. Interestingly, MIM160 plants showed worse adaption to heat. In addition, arf10, arf16, and arf17 mutants presented similar phenotypes to 160OE under heat stress to advance abilities of thermotolerance. Moreover, transcriptome and qRT-PCR analyses revealed that HSP17.6A, HSP17.6II, HSP21, and HSP70B expression levels were regulated by heat in 160OE, MIM160, arf10, arf16, and arf17 plants. Hence, miR160 altered the expression of the heat shock proteins and plant development to allow plants to survive heat stress.